Efficient biolistic transformation of the moss Physcomitrella patens - M. Šmídková; M. Holá; K. J. Angelis (Biologia Plantarum, 2010)
High rates of homologous recombination (HR) in comparison to other plants make the moss Physcomitrella patens an attractive model organism for genetic studies as well as biotechnological applications. We describe a simple protocol for the efficient biolistic transformation of protonemal tissue with minimum tissue handling steps. The transformation efficiency depends on the biolistic conditions. The bombardment of tissue with 1 μm gold particles yielded between 20 and 40 stable transformants per 1 μg of DNA. Transformation with circular plasmids generates higher frequencies of random transgene integration, whereas linear plasmids are more efficient in generating gene-targeted insertions.